PENDIDIKAN BERBASIS TEKNOLOGI - Panuah, Yulisar; Haryadiyanto, Haryadiyanto (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
ICT-based education development needs to be serious thought of various parties, and needs a structured strategy with certainly focused stages towards quality improvement efforts of education that are equally global so that our education is not more deteriorated between progress of education in a world that is based on information and communication technology there must be a tiered scenario in the application of a mouse based education model that is based on the ability of schools to absorb and implement information and communication technology. government regulations that encourage school climate, teachers, employees, students to be able to change the absolute conventional learning paradigm relying on teachers, becoming modern learning that puts teachers as learning facilitators and motivators, and progress of information and communication technology as learning tools. gradually school what is involved in ICT-based education should increase in the utilization of ICT for learning, need strong teacher commitments, strong schools, which can be seen from infrastructure support, learning content support, support to accelerate mastery of teachers among teachers, and staff administrator support from schools. supporting infrastructure needs to be formed such as the division of the center for ICT-based education, both at the provincial, district level, and administrators in schools, to organize the application of the ICT-based education system.